Management of Ralstonia solanacearum in eucalyptus seedlings: initial studies with Trichoderma harzianum and Purpureocillium lilacinum - Gomes, Marcela Eloi [UNESP]; da Silva Souza, Lucas [UNESP]; dos Anjos, Louyne Varini Santos [UNESP]; Antonio, Gabriel Leonardi [UNESP]; Furtado, Pedro Ozi; de Souza, Victor Hugo Moura; Bergamini-Lopes, Marcela Pagoti [UNESP]; Pascholati, Sergio Florentino; Firmino, Ana Carolina [UNESP] (My University, 2023)
The study evaluated the effectiveness of Trichoderma harzianum and Purpureocillium lilacinum in the management of Ralstonia solanacearum on eucalyptus seedlings. For each biological control agent, the following treatments were conducted: plants with their roots immersed in a cell suspension of the biological control agent (SI+I); plants in pots containing the biological control agent in hydrogel (SI+H); plants in pots previously drenched with the biological control agent (SI+IR), and plants in pots where the biological control agent was applied directly into the planting hole (SI+PO). Control treatments consisted of plants in pots infested and pots not infested with R. solanacearum (PC and NC, respectively). All treatments were carried out with two eucalyptus clones (SR and 144). The analyzed variables were mortality rate of eucalyptus seedlings and dry weight of plants. The most effective treatment had the activity of peroxidase, polyphenol oxidase and phenylalanine ammonia-lyase (PAL) measured at 7, 14 and 21 days after inoculation. The method of incorporating the biological control agent influenced R. solanacearum control. Results revealed that SI+H and SI+IR were the most effective treatments. Using T. harzianum, mortality was only 12% for clone SR and 0% for clone 144 in the treatments SI+H and SI+IR, respectively. In the treatment SI+H, using P. lilacinum, 25% and 20% dead seedlings were obtained for clone SR and clone 144, respectively. Both biological agents increased the dry mass of plants. The activity of peroxidase, polyphenol oxidase and PAL was higher at 14 days after inoculation with T. harzianum in the treatments SI+IR and SI+H, for clones SR and 144, respectively. Using T. harzanium can serve as a support for the sustainable management of areas where cases of R. solanacearum have previously occurred.
Manejo de Ralstonia solanacearum em mudas de eucalipto: estudos iniciais com Trichoderma harzianum e Purpureocillium lilacinum
Keywords: Biological control; Forestry; Resistance induction